ADOPTED CHILDREN & HEIRS: THE PROBLEMATICS OF ABUSE OF THE LAW IN INHERITANCE - Tashya Panji Nugraha; Naufal Fakhri Ghozali; Kelik Wardiono; Marisa Kurnianingsih (Universitas Muhammadiyah Tangerang, 2023)
THIS study aims to analyze the position of adopted children to the inheritance of their adoptive parents as well as to discuss how this position can be if there is a violation of law during the adoption which causes problems with the existing inheritance. The type of this research is descriptive research with a normative approach. Based on this research, the position of adopted children to the inheritance of their adoptive parents is strongly influenced by which type of law is used in the practice of adoption because Western law, Islamic law, and customary law that apply as the basis for adoption in Indonesia have different provisions. Then, if it is found that there has been a violation of law in the adoption of a child which causes problems with inheritance, the judge will identify the problem based on the facts and consider it based on the law used to adopt the adopted child so that the result decision can provide a sense of justice, benefits, as well as legal certainty or in other words an ideal decision.